Funções: propostas para o ensino na educação básica através do software GeoGebra e da resolução de problemas - CUNHA, Jaqueline de Fátima Vieira (2017)
Math is very present in people’s lives. In the case of functions, they are used in different aspects of human activity, such as in physics, chemistry, biology, and economics. However, in many cases when teaching the content, the teacher uses methods that lead students to work only on definitions, forms and rules, making the content of functions difficult and purposeless. Therefore, this work presents differentiated methodologies that aim to enable a better understanding of the concepts to be studied and to motivate students, improving learning. First, from chapters 2 to 6, we present the definitions, formulas and construction of graphs of polynomial, muddy, exponential, and logarithmic functions. But, the main focus of the work is the chapters 7 and 8. Chapter 7 presents suggestions of activities with computational resources, to be executed by the teacher, to make the classes more interesting and motivating. For the execution of the activities, we use the free software GeoGebra (version 5.0) and the knowledge of functions in the construction of drawings. In this way, we explore the knowledge of the theory of functions and their graphs in a different way and that arouses the interest of the student. Finally, chapter 8 presents situations of students’ daily life that are solved with the support of functions, showing that the content is very important and has several applications in the day by day.